PROFIL KEAMANAN METFORMIN PADA PASIEN DIABETES MELITUS TIPE DUA DENGAN INFEKSI COVID - 19: TINJAUAN SISTEMATIS - Veriantara Satya Dhika, (2021)
Diabetes Mellitus (DM) type two is a challenge for the management of COVID-19. Metformin is the treatment of choice for DM type two patients with COVID-19. At this time, there are no studies related to how the safety aspects of these drugs are used in DM type two patients with COVID-19. This study aims to determine the safety profile of metformin in DM type two patients with COVID-19. The method used is systematic with a combination of data from several different database articles, namely PubMed, Medline (Ovid), ScienceDirect, Cochrane Library, ClinicalTrials. gov, and medrxiv.org. A total of 23 study articles from 2020-2021 meet the inclusion criteria and are of very good quality. The results of this study indicate a sufficient safety profile in terms of mortality, good life, hospital and ICU admissions, several comorbidities, risk of complications, diagnosis and severity. Based on its safety profile, metformin remains a definite use for type 2 DM patients with COVID-19 infection.